Pelaksanaan Kurban Mayit Menurut Imam An-Nawawi dan Imam Ibnu At-Taimiyah Studi Kasus Desa Tanjung Baru Kecamatan Tanjung Morawa - Elika, Dinda; Mukhsin, Abd. (Nagari Law Review, 2024)
This research examines the implementation of sacrificial services for the deceased, a practice that has sparked differing opinions among Islamic scholars. The background of this issue stems from varying interpretations of religious evidence and jurisprudential understanding between Imam An-Nawawi and Imam Ibn Taymiyyah. The research questions are: (1) What are the views of Imam An-Nawawi and Imam Ibn Taymiyyah regarding sacrifice for the deceased? (2) What legal bases and arguments are used by these two imams? (3) How is this practice implemented in the community of Tanjung Baru Village, Tanjung Morawa District? The research method employed is a comparative empirical normative sociological study. Primary data was obtained directly from the works of Imam An-Nawawi and Imam Ibn Taymiyyah, as well as through observations and interviews at the research site. Data analysis was conducted qualitatively using a comparative approach The results reveal significant differences between the views of the two imams. Imam An-Nawawi permits sacrifice for the deceased, both with and without a will, based on hadiths about giving charity for the dead. Meanwhile, Imam Ibn Taymiyyah rejects this argument and holds a different perspective. In Tanjung Baru Village, the practice of sacrifice for the deceased is still carried out by some community members, although understanding of its legal basis varies. This study suggests the need for further education of the community about the variety of scholarly opinions on this matter, and encourages dialogue among local religious leaders to achieve a more comprehensive understanding.